Forces applied at the footrest during ergometer kayaking among female athletes at different competing levels - a pilot study - Å. B. Tornberg; P. Håkansson; I. Svensson; P. Wollmer (BMC, 2019)
Abstract Background Power output and force development during exercise are thought to be important indices of performance in elite athletes. The aim of this preliminary study was to determine the forces applied at the footrest during ergometric kayaking in individual kayakers at different competitive levels. Methods Three elite female kayakers participated voluntarily in the study. Oxygen consumption (VO2) and mean power were measured during paddling at three different work levels (15 W below onset of blood lactate accumulation (OBLA), at OBLA, 15 W above OBLA and all-out paddling) on a modified kayak ergometer. External force sensors were attached to the wires on right and left side connecting the paddle to the flywheel of the kayak ergometer. Individual footrests were built to enable measurements of pushing and pulling forces and to distinguish between the left and right foot. Result The relative differences between the three athletes were similar for power, VO2peak and forces at the paddle. There were, however, differences in the forces applied at the footrest, where the most accomplished paddler generated forces 3 to 26 times as high as the least accomplished paddler. Conclusion The relative differences between the three athletes were similar for power, VO2 and forces at the paddle. There were, however, dramatic differences in the forces applied at the footrest.